A Sufi-Neuroplasticity Model for Muslim Students' Emotional Regulation - Rahmat Lutfi Guefara; Aryadi Nursantoso; Rohmat Rohmat; Novan Ardy Wiyani; Razka Zhorif alqushoyyi (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2025)
Emotional regulation has become a pressing concern in Islamic higher education. Muslim students now face academic pressure, digital exposure, social anxiety, and unstable psychological responses in everyday learning. Previous studies have discussed Islamic education, Sufism, spirituality, mindfulness, religious coping, and emotion regulation. However, only a limited body of work has built a conceptual model that links Sufi practices with neuroplasticity for Islamic educational purposes. This article presents the Sufi-Neuroplasticity Model as a theoretical framework to enhance the emotional regulation of Muslim students. The study was qualitative library research that reviewed classical Sufi literature and Scopus-indexed studies (2020-2025) in the fields of Islamic education, Sufi pedagogy, neuroeducation, Islamic psychology, emotion regulation and Islamic mindfulness. The collected data were analyzed through content analysis and conceptual synthesis. The findings show that dhikr, muraqabah, tawakkul, khauf transformation, and rida can be conceptualized as spiritual-pedagogical practices related to repetition, reflective awareness, cognitive meaning reconstruction, fear reorientation, and emotional acceptance. The model contributes to Islamic education by positioning Sufism as a transformative pedagogy for emotional self-regulation, while avoiding direct neurological or clinical claims.